Analisis Pengungkapan Corporate Social Responsibility (CSR) Pada Perusahaan Industri Pertambangan Yang Terdaftar Di BEI Periode 2018–2022 - Tri Prastiyo Agung Nugroho; Kartika Hendra Titisari; Suhendro (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
With the research variables company size, profitability, board size, and leverage, this study intends to determine the effect of corporate social responsibility (CSR) disclosures on mining industry companies listed on the Indonesia Stock Exchange (IDX) with a range of observation years 2018–2022. Annual reports and sustainability reports from mining sector companies collected from the websites of each company are used as secondary data for this study. Eleven companies were selected by sampling using a purposive sampling technique and were used as research samples because they met the sampling criteria. Multiple linear regression analysis technique is used in the data analysis method. Based on the results of hypothesis testing, corporate social responsibility disclosures are not affected by company size, profitability, or leverage variables, while board size has an influence on corporate social responsibility disclosures.